1994
DOI: 10.1128/mcb.14.2.1431
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of the cDNA encoding a novel human pre-B-cell colony-enhancing factor.

Abstract: A novel gene coding for the pre-B-cell colony-enhancing factor (PBEF)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
800
3
17

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 900 publications
(834 citation statements)
references
References 32 publications
14
800
3
17
Order By: Relevance
“…The specificity of the NAMPT antibody was validated as detailed in the methods and Supplementary Figure 2. NAMPT was expressed in certain normal tissues with the highest level in liver, pancreas, adrenal gland and muscle (Supplementary Figure 3A), consistent with previous reports (Samal et al, 1994;Fukuhara et al, 2005). We found that NAMPT expression was upregulated in many cancer types including prostate, colon, brain and lung cancer, as well as lymphoma when compared with their normal counterparts, with prostate exhibiting the most consistent and striking difference between normal tissue and cancer in arrays obtained from different sources (Figure 1c and Supplementary Figure 3B).…”
Section: Nampt Is Overexpressed In Human Prostate Cancersupporting
confidence: 92%
See 1 more Smart Citation
“…The specificity of the NAMPT antibody was validated as detailed in the methods and Supplementary Figure 2. NAMPT was expressed in certain normal tissues with the highest level in liver, pancreas, adrenal gland and muscle (Supplementary Figure 3A), consistent with previous reports (Samal et al, 1994;Fukuhara et al, 2005). We found that NAMPT expression was upregulated in many cancer types including prostate, colon, brain and lung cancer, as well as lymphoma when compared with their normal counterparts, with prostate exhibiting the most consistent and striking difference between normal tissue and cancer in arrays obtained from different sources (Figure 1c and Supplementary Figure 3B).…”
Section: Nampt Is Overexpressed In Human Prostate Cancersupporting
confidence: 92%
“…In mammals, NAD þ can be biosynthesized from nicotinamide (NAM), nicotinic acid or tryptophan, with NAM as the primary precursor (Garten et al, 2009). The rate limiting step for NAD þ biosynthesis from NAM is the transfer of a phosphoribosyl group to NAM, which is catalyzed by nicotinamide phosphoribosyltransferase (NAMPT) (Revollo et al, 2004), also known as pre-B-cell colony enhancing factor (Samal et al, 1994). NAMPT has a crucial role for growth factor-induced myeloid differentiation (Skokowa et al, 2009), circadian clock (Nakahata et al, 2009;Ramsey et al, 2009), glucose-restriction-impaired skeletal myoblast differentiation (Fulco et al, 2008) and insulin secretion in pancreatic beta cells (Revollo et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Although the PBEF protein lacks a classic signal sequence for secretion, it is constitutively released and detected in conditioned medium from many cell types (12,13,(33)(34)(35)(36)(37). PBEF is detectable in serum and synovial fluid (1,6), and the levels of PBEF have been found to be increased in patients with rheumatoid arthritis, in whom it is clinically correlated with the Disease Activity Score in 28 joints and elevated C-reactive protein level (1,2,6).…”
Section: Discussionmentioning
confidence: 99%
“…Although PBEF has been regarded as an adipose tissue-related hormone, studies show that PBEF is ubiquitously expressed in the body. Among different human tissues, the maximum gene expression was found in the liver and peripheral blood leukocytes [6,22]. A large-scale analysis of the human transcriptome indicated that the PBEF gene is highly expressed in whole blood, over 100 times of the median abundance, while the expression in adipocytes is just about 2 times of the median abundance (GEO series GSE1133) [23].…”
Section: Discussionmentioning
confidence: 99%
“…Visfatin is a rediscovery of the cytokine-like protein pre-B cell colony-enhancing factor 1 (PBEF 1 ) [6]. It was also identified as cytosolic nicotinamide phosphoribosyltransferase (NAMPT), demonstrated by in vitro, in vivo, and structural studies [7][8][9].…”
Section: Introductionmentioning
confidence: 99%